Detected some virulence factors of Corynebacteria isolated from ruminants (Global Journal of Medical Research, 2023)
Background Ruminants suffer from suppurative infections caused by the corynebacteriaceae affecting animals and humans They cause severe economic losses and a high culling rate with poor treatment efficacy Objectives The present study aimed for isolation and identification of Corynebacterium species from ruminants Antimicrobial sensitivity and detection for some virulence factors were done Methods Two hundred and fifteen samples were gathered from various abscess locations in different species inoculated on Baird Parker agar with 1 tween 80 then identified by biochemical tests Antimicrobial sensitivity by MIC test was done with levofloxacin Zinc oxide Nanoparticles and Egyptian propolis extraction Some isolates of Corynebacterium Pseudotuberculosis were identification of by 16Sr RNA PCR Results Positive suspected isolates were 22 isolates for Corynebacterium C pseudotuberculosis whilst 5 isolates for Trueperella T pyogenes as they grow as small dark grey opaque colonies C pseudotuberculosis was positive for esculin urease catalase Ellman and Beta-D-Fucosidase while T pyogenes was negative for them All isolates showed phenotypic virulence factors such as hemolysin and lipase enzymes with lecithinase activity and biofilm formation Antimicrobial sensitivity showed sensitivity to levofloxacin and resistance to the other while showing anti-biofilm formation at the same concentration 8 isolates of C pseudotuberculosis were sequenced and recorded in the gene bank with accession number ON899860